2017
DOI: 10.1037/apl0000154
|View full text |Cite
|
Sign up to set email alerts
|

Helping employees sleep well: Effects of cognitive behavioral therapy for insomnia on work outcomes.

Abstract: Drawing from recent research advances indicating the harmful effects of insomnia on negative affect, job satisfaction, self-control, organizational citizenship behavior, and interpersonal deviance, we hypothesized that treating insomnia with Internet based cognitive behavior therapy for insomnia would lead to improvements in these outcomes. In a field experiment with a randomized wait-list control group, we found that treatment had a beneficial direct effect on negative affect, job satisfaction, and self-contr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
92
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 106 publications
(94 citation statements)
references
References 58 publications
2
92
0
Order By: Relevance
“…Specifically, research on the biological or physiological factors that augment or dampen entrepreneurial motivation is largely absent. This is a noteworthy oversight as sleep (Murnieks et al, in press; Barnes, ; Barnes, Miller, & Bostock, ; Gunia, ), testosterone (Nicolaou, Patel, & Wolfe, ), and cortisol levels (Liu‐Qin, Bauer, Johnson, Groer, & Salomon, ; Sherman, Lemer, Josephs, Renshon, & Gross, ) represent factors that may explain meaningful variance in entrepreneurial motivation and draw increasing interest in the OB literature but are understudied in entrepreneurship. More theory and measurement of these individual variables could expand our understanding of the role of physiology in entrepreneurial motivation and also contribute to the OB literature.…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, research on the biological or physiological factors that augment or dampen entrepreneurial motivation is largely absent. This is a noteworthy oversight as sleep (Murnieks et al, in press; Barnes, ; Barnes, Miller, & Bostock, ; Gunia, ), testosterone (Nicolaou, Patel, & Wolfe, ), and cortisol levels (Liu‐Qin, Bauer, Johnson, Groer, & Salomon, ; Sherman, Lemer, Josephs, Renshon, & Gross, ) represent factors that may explain meaningful variance in entrepreneurial motivation and draw increasing interest in the OB literature but are understudied in entrepreneurship. More theory and measurement of these individual variables could expand our understanding of the role of physiology in entrepreneurial motivation and also contribute to the OB literature.…”
Section: Discussionmentioning
confidence: 99%
“…The SCI has subsequently been translated, and validated further in Italian, Romanian, Chinese and French (Bayard et al ., ; Palagini et al ., ; Voinescu and Szentagotai, ; Wong et al ., ). The SCI has demonstrated sound psychometric properties previously, including internal consistency (published range: α = 0.71–0.89), convergent validity with the Pittsburgh Sleep Quality Index ( r = 0.73) and the Insomnia Severity Index ( r = 0.79), predictive validity in relation to insomnia disorder when diagnosed by expert clinical interview (Bayard et al ., ; Palagini et al ., ; Wong et al ., ) and has proved sensitive to change in several clinical trials (Barnes et al ., ; Bostock et al ., ; Espie et al ., ; McGrath et al ., ). Secondly, we will present sex‐ and age‐referent data on a sample of 200 000 people to facilitate the use in clinical and research settings.…”
Section: Introductionmentioning
confidence: 99%
“…Relatedly, recent research has shown the effects of internet‐based cognitive behavioural treatments for insomnia (Barnes, Miller, & Bostock, ) and CPAP devices for obstructive sleep apnoea (Carleton, Barling, & Driver, ) on workplace behaviours. Future research might now investigate whether these or other treatments for sleep problems and sleep disorders (e.g., sleep hygiene and stimulant medication) might minimize the indirect effects of ADHD symptoms on passive leadership.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, organizations can best affect the indirect effects of leaders' ADHD symptoms on passive leadership by helping to limit the sleep problems that result in daytime sleepiness. Although concern is often expressed that doing so would consume valuable organizational resources (e.g., Litwiller et al, ), this is not necessarily the case: Recent research endorses the indirect effects of low‐cost, internet‐based cognitive behavioural therapy for insomnia on interpersonal deviance and organizational citizenship at work (Barnes et al, ) and readily accessible, validated treatments for obstructive sleep apnoea (Carleton et al, ) on work withdrawal (e.g., cognitive distraction and partial absenteeism).…”
Section: Discussionmentioning
confidence: 99%